High rate direct current magnetron sputtered and texture-etched zinc oxide films for silicon thin film solar cells - T. Tohsophon (2018)
Aluminum-doped zinc oxide (AZO) films were prepared by in-line direct current (dc) magnetron sputtering on glass substrates. Four types of ceramic targets with 0.5 wt.% or 1 wt.% of aluminum oxide and different preparation methods, namely normal sintered, soft sintered and hot pressed, were employed. The influence of different target manufacturing processes, aluminum concentration and sputtering conditions on AZO films were investigated. Depending on the type of targets and deposition conditions, highly transparent films with low resistivity values in the range of 3.6-11 × 10- 4 Ω cm were obtained. The etching behaviour in hydrochloric acid and the resulting light scattering properties of the AZO films were strongly influenced by the choice of the target and the deposition conditions. The most favourable films have been successfully applied in thin film solar cells with 1.1-μm microcrystalline silicon absorber layer leading to an initial efficiency of 7.8%. © 2007 Elsevier B.V. All rights reserved.